1999
DOI: 10.1002/(sici)1520-6300(199911/12)11:6<763::aid-ajhb6>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasitic infection, anthropometrics, nutritional status, and physical work capacity in Colombian boys

Abstract: This article tests the hypothesis that the presence of gastrointestinal parasites in Colombian boys is negatively associated with anthropometric characteristics, physical work capacity, blood hemoglobin (Hb) levels, and nutritional status. Anthropometric, Hb, V . O 2 max, and parasite load data were collected on 1,016 boys in Cali, Colombia. The boys were classified as lower socioeconomic class (SEC) from either urban or rural environments, and upper SEC from an urban environment. Sixty-three percent of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
0
12
0
5
Order By: Relevance
“…The nutritional consequences of parasitic infection have also been documented in diverse contemporary populations. For example, in Columbia (Wilson et al, 1999) found that parasitic infection was associated with stunting and reduced work capacity among youth. Similarly, in the Amazon region of Peru helminth infections were associated with stunting among both children under 2 years of age (Gyorkos et al, 2011) and school-age children (Casapia et al, 2006) in a poor community.…”
Section: Parasitism and Disease Stressmentioning
confidence: 92%
“…The nutritional consequences of parasitic infection have also been documented in diverse contemporary populations. For example, in Columbia (Wilson et al, 1999) found that parasitic infection was associated with stunting and reduced work capacity among youth. Similarly, in the Amazon region of Peru helminth infections were associated with stunting among both children under 2 years of age (Gyorkos et al, 2011) and school-age children (Casapia et al, 2006) in a poor community.…”
Section: Parasitism and Disease Stressmentioning
confidence: 92%
“…La malnutrición proteica en poblaciones transicionales, como las aquí estudiadas, ha sido asociada a altas cargas parasitarias 4 y la relación entre infecciones por geohelmintos, malnutrición y anemia ha sido demostrada por diversos autores 6,7,8,32,33 . El elevado grado de parasitismo intestinal, junto a la presencia constante de otras enfermedades infecciosas como las respiratorias agudas, diarreas, etc., podrían contribuir al surgimiento de cuadros de anemia y/o malnutrición proteica en estas poblaciones.…”
Section: Tablaunclassified
“…Esta situación, unida al sedentarismo y la deficiente atención de la salud, favoreció la transmisión de infecciones parasitarias en esas poblaciones 3,4 . Por otra parte, también las infecciones parasitarias causan o agra- van la malnutrición y provocan un retraso en el crecimiento de los individuos infectados 5,6,7,8 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Malabsorption of fat, D-xylose, vitamin A and vitamin B12 have been reported associated with this infection 3,12,34,47 . Chronic giardiasis in children is generally associated with clinical manifestations of failure to thrive 1,9,48,53 . The association of giardiasis with proteinenergy malnutrition (PEM) and micronutrient deficiency, and more recently with iron deficiency anemia (IDA), has been reported by some researchers 1,6,9,26,29,40,42,48 .…”
Section: Introductionmentioning
confidence: 99%